ORGANIZATIONAL RESILIENCE AND EMPLOYEE PERFORMANCE IN CRISIS ECONOMY - George, Yebimodei Esther; Odubo, Agonimi (International Journal of Innovations in Engineering Research and Technology, 2024)
The aim of the study was to critically analyze the significance of organizational resilience on employee performance, especially during crisis situation, such as the recent Covid-19 pandemic that keep all the nations and business organizations in a state of chaos It could be seen that firms all over the world are crying wolf due to the loss of manpower, low profitability, low productivity, poor service delivery and so on, as a result of the Covid-19. The cause of the low performance could be attributed to not being pro-active by the employees, or non-anticipation of perturbations, inability to learn from experience, inability to adapt and dynamic capability to work in any given environment and changes in policies and programmes as the situation demand to achieve organizational sustainability. Therefore, organizational resilience is the ability of organizations to prepare, absorb shock or develop resistance in the face of perturbations within its environment, and surmount all insurmountable to move to a better next level. The study concluded that organizational learning, adaptive capacity and dynamic capability have significant relationship with employee performance. Hence, the study recommended that management should foster conducive organizational learning, adaptive capacity and dynamic capability, as these will equip the employees to remain with the organization, and put up their best work effort for increased productivity and profitability.